2002
DOI: 10.5194/hess-6-819-2002
|View full text |Cite
|
Sign up to set email alerts
|

The mineralogy and chemistry of fine-grained sediments, Morphou Bay, Cyprus

Abstract: The mineralogy and chemistry of the less than 20µm fraction of marine sediments at Morphou Bay, north-west Cyprus, are presented to characterise fine-grained sediment supplies from basic and ultrabasic rocks of the Troodos Massif within a typological setting. The sediments comprise a mixture of smectite, illite, kaolinite and iron rich chlorite. They also contain amorphous iron oxides/hydroxides, calcite (with some magnesium substitution for calcium) and an amphibole. Spatial patterns in mineralogy occur: the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Morphologically, the Mesaoria Plain lies at a maximum height of 300 m.a.s.l (metres above sea level) and is bounded by the Kyrenia range to the north, with elevations of up to 910, and the Troodos massif to the south, with heights of up to 1940 m.a.s.l. (Neal, 2002).…”
Section: Geological Settingmentioning
confidence: 95%
“…Morphologically, the Mesaoria Plain lies at a maximum height of 300 m.a.s.l (metres above sea level) and is bounded by the Kyrenia range to the north, with elevations of up to 910, and the Troodos massif to the south, with heights of up to 1940 m.a.s.l. (Neal, 2002).…”
Section: Geological Settingmentioning
confidence: 95%
“…4). Potassium will be associated with clay minerals, illite in particular, rather than in the calcite lattice (Neal 2002). Potassium and Al are associated with clay minerals and Sr has a close relationship with these two metals indicating that these three metals derive from a natural geogenic source rather than an anthropogenic one.…”
Section: Paleoweatheringmentioning
confidence: 98%
“…The results showed that relatively higher metal concentrations were obtained at Gazi Magusa area. Moreover, it was reported that the highest Ni values at Girne area could be due to the transported erosion products coming from the surroundings of the ophiolithic rocks at Cyprus (Neal, 2002).…”
Section: Metal-enrichment Factors (Ef)mentioning
confidence: 99%